PHYTOSOCIOLOGY OF A LOWER MONTANE FOREST ON MT. BATULANTEH, SUMBAWA, INDONESIA - Muhammad Mansur; Kuswata Kartawinata (BRIN Publishing (Penerbit BRIN), 2017)
MANSUR, M & KARTAWINATA, K. 2017. Phytosociology of a Lower Montane Forest on Mt. Batulanteh, Sumbawa, Indonesia. Reinwardtia 16 (2): 77-92. — While Indonesia’s forests are globally known for their high species diversity but many regions remain little known to investigate the tree community in a lower montane forest at Mt. Batulanteh in Sumbawa. We subjectively laid out plots of 1,800 m2 each, two in secondary forests and one in a disturbed primary forest. All stems over 5 cm diameters were measured and identified. In the plot of 0,54 hectare, we recorded 723 individuals, representing 78 species, 60 genera and 33 families. Estimated volume of boles was 183.2 m3/0.54 ha, biomass was 220.1 tons/0.54 ha, carbon stock was 110.0 tons/0.54 ha and CO2 sequestration was 403.1 ton/0.54 ha. The forest at Mt. Batulanteh is classified as Garcinia-Cryptocarya association consisting of Micromelum-Cinnamomum subassociation. Dipterocarpus-Calophyllum subassociation and Garcinia-Syzygium subassociation. Dominant species were Micromelum minutum (IV=27.24), Mallotus philippensis (IV=26.2), Cryptocarya ferrea (IV=24.71) and Cinnamomum burmanni (IV=23.81) in Plot 1, Dipterocarpus retusus (IV=77.4) and Calophyllum soulattri (IV=24.21) in Plot 2, and Garcinia celebica (IV=34.86) and Syzygium sp. 1 (IV=34.76) in Plot 3. Dipterocarpus retusus was unique of having restricted distribution. Fagaceae, typical family in montane forests, was absent. Shannon’s diversity index was low (H '= 1.61). It can be concluded that the plots do not constitute a representative of Mt. Batulanteh and the surrounding forests, but they were sufficient to provide an illustration of the forests locally. The diameter class distribution indicated that the forests were regenerating. They were developing secondary forest and regenerating disturbed primary forest; slow successions were in the process and could be enhancedby ecological restoration. Further botanical explorations in poorly known regions of Sumbawa should be intensified further.